2012
DOI: 10.1007/s00423-012-1028-3
|View full text |Cite
|
Sign up to set email alerts
|

Deviation from a preoperative surgical and anaesthetic care plan is associated with increased risk of adverse intraoperative events in major abdominal surgery

Abstract: Surgery was more difficult than expected in up to one out of five cases. In a similar proportion, disagreement between preoperative care plans and observed clinical management was independently associated with an increased risk of adverse clinical events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Resulting deviations from preoperative surgical or anesthetic plan were frequently due to organizational and team-related events, and were independently associated with adverse clinical events. 29 In accordance with this report, risk-adjusted morbidity correlated with levels of communication and collaboration in surgical teams in a large multicentre survey of surgical staff. 30 More generally, a recent systematic review of studies mainly from perioperative settings concluded that team processes actually do influence clinical team performance as well as actual patient outcomes according to some investigations.…”
Section: General Principles Of Leadership and Co-ordination In Teamssupporting
confidence: 84%
See 1 more Smart Citation
“…Resulting deviations from preoperative surgical or anesthetic plan were frequently due to organizational and team-related events, and were independently associated with adverse clinical events. 29 In accordance with this report, risk-adjusted morbidity correlated with levels of communication and collaboration in surgical teams in a large multicentre survey of surgical staff. 30 More generally, a recent systematic review of studies mainly from perioperative settings concluded that team processes actually do influence clinical team performance as well as actual patient outcomes according to some investigations.…”
Section: General Principles Of Leadership and Co-ordination In Teamssupporting
confidence: 84%
“…28 Even if formal briefings are instituted to facilitate communication within and between teams, the factual quality of communication is not warranted. 29 A recent study presented a system of preoperative weekly interdisciplinary meetings of senior staff from surgery, anesthesia, radiology, oncology, and nursing, to ensure shared understanding of the surgical plans and risks of elective cases. Despite these meetings, mutual critical information (surgical difficulty and estimated blood loss; anesthetic monitoring) was lacking or inaccurate in 15e20% of cases.…”
Section: General Principles Of Leadership and Co-ordination In Teamsmentioning
confidence: 99%
“…The virtual exploration may assist the surgeon during the preliminary phase of a surgical procedure, through interactive and visual planning of the operative strategy, which can be simulated and corrected at every step. A recent paper [6] reported that disagreement between preoperative care plans and observed clinical management was independently associated with an increased risk of adverse clinical events. Deviations are rather underestimated and occur in approximately 20 % of cases.…”
Section: Introductionmentioning
confidence: 97%
“…AR is a promising technology, which may provide guidance to dissection and help counterbalance the lack of tactile feedback due to the use of long laparoscopic instruments to manipulate tissues specific to minimally invasive laparoscopic surgery, with or without robotic assistance. At our institute, AR guidance was pioneered with laparoscopic adrenal tumor resection [6] using a customary software (VR-RENDER®) to construct the virtual model of the patient. The system allowed a very accurate navigation with a maximum error of 2 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is acknowledged that maternal and neonatal clinical outcomes were not presented, and nor were patient experience outcomes or the feedback from clinicians. Despite no maternal or neonatal outcomes presented, noting there are no published studies showing a correlation between documenting prenatal care plans and safety/quality in maternity care, there are noteworthy examples in primary care amongst surgical patients and in those with diabetes and established coronary heart disease, where the use of detailed care plans has been associated with superior clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%